2014
DOI: 10.1007/s00432-014-1622-6
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic bilateral salpingectomy (PBS) to reduce ovarian cancer risk incorporated in standard premenopausal hysterectomy: complications and re-operation rate

Abstract: PBS did not increase the complication rate and reduced the incidence of adnexal pathologies requiring surgical re-intervention. Prospective trials should clarify the impact of PBS on cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 30 publications
2
50
0
3
Order By: Relevance
“…To date, no large case controlled or epidemiological studies exist to provide concrete evidence for a potential early menopause after prophylactic salpingectomy. The peri-operative morbidity of performing a salpingectomy at the time of hysterectomy is not significantly increased compared to hysterectomy alone [28]. Failure to remove the tube at hysterectomy or during sterilisation, however, may be associated with potential disadvantages such as the development of a hydrosalpinx.…”
Section: Morbidity Of Prophylactic Adnexal Surgerymentioning
confidence: 91%
“…To date, no large case controlled or epidemiological studies exist to provide concrete evidence for a potential early menopause after prophylactic salpingectomy. The peri-operative morbidity of performing a salpingectomy at the time of hysterectomy is not significantly increased compared to hysterectomy alone [28]. Failure to remove the tube at hysterectomy or during sterilisation, however, may be associated with potential disadvantages such as the development of a hydrosalpinx.…”
Section: Morbidity Of Prophylactic Adnexal Surgerymentioning
confidence: 91%
“…Finally, we did not model costs associated with potential morbidity from salpingectomy, because these were not likely to be different from the alternatives (hysterectomy alone or tubal ligation) 22-25 nor did we include costs of recurrent ovarian cancer given the wide variety of scenarios and treatment options. We did not model subsequent adnexal cysts, which would be more prevalent after hysterectomy alone, 25 the increased risk of osteoporosis and other cancers after hysterectomy with BSO, 6 or ectopic pregnancies after tubal ligation. 43 However, inclusion of these would yield an even greater difference favoring salpingectomy in terms of lifetime effectiveness and costs.…”
Section: Discussionmentioning
confidence: 99%
“…22 The additional operative time required for salpingectomy was insignificant, 23 and perioperative complications and length of hospitalization were not increased compared with hysterectomy alone. [22][23][24][25] There is no available data on the rate of inadvertent oophorectomy at the time of salpingectomy. Based on the FinHyst prospective study, in which only "a few" unintended oophorectomies occurred during 3,600 abdominal and vaginal hysterectomies, we estimated a 1% risk of inadvertent oophorectomy during salpingectomy.…”
Section: Methodsmentioning
confidence: 99%
“…These studies reveal no difference in average operating time, estimated blood loss, intraoperative complications, and postoperative complications. 29,30 One study specifically compared tubal ligation with bilateral salpingectomy, including open postpartum salpingectomy and salpingectomy done at the time of cesarean section. 31 Investigators found that compared with tubal ligation, bilateral salpingectomy increased operating room time by 10.2 minutes but did not increase length of hospital stay.…”
Section: Opportunistic Salpingectomymentioning
confidence: 99%